2004
DOI: 10.1126/science.1094285
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Roles of Ventral and Dorsal Striatum in Instrumental Conditioning

Abstract: Instrumental conditioning studies how animals and humans choose actions appropriate to the affective structure of an environment. According to recent reinforcement learning models, two distinct components are involved: a "critic," which learns to predict future reward, and an "actor," which maintains information about the rewarding outcomes of actions to enable better ones to be chosen more frequently. We scanned human participants with functional magnetic resonance imaging while they engaged in instrumental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

162
1,458
6
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,884 publications
(1,630 citation statements)
references
References 26 publications
162
1,458
6
4
Order By: Relevance
“…More specifically, changes in state values V MF (s) imply changes in future reward, and so a change in value induced by an action is a metric that can be used to reinforce behaviours. This forms the core of the actor-critic model (Barto et al, 1983;O'Doherty et al, 2004). Experimentally, it is perhaps most directly demonstrated by conditioned reinforcement experiments (Everitt and Robbins, 2005;Meyer et al, 2012), where instrumental behaviours can be reinforced by Pavlovian CSs.…”
Section: Instrumental Behaviourmentioning
confidence: 98%
“…More specifically, changes in state values V MF (s) imply changes in future reward, and so a change in value induced by an action is a metric that can be used to reinforce behaviours. This forms the core of the actor-critic model (Barto et al, 1983;O'Doherty et al, 2004). Experimentally, it is perhaps most directly demonstrated by conditioned reinforcement experiments (Everitt and Robbins, 2005;Meyer et al, 2012), where instrumental behaviours can be reinforced by Pavlovian CSs.…”
Section: Instrumental Behaviourmentioning
confidence: 98%
“…Actions that produce positive prediction errors are reinforced, whereas those that produce negative prediction errors are punished. Commonly, the critic is assigned to ventral striatum and the amygdala (Hazy, Frank, & O'Reilly, 2010;O'Doherty et al, 2004), whereas the actor is considered to be instantiated by dorsal striatal interactions with pre/motor cortex.Critic learning. The critic in our model is similar to that in classical formulations (but see Discussion).…”
mentioning
confidence: 99%
“…Neuroimaging studies of reward processing have identified a number of brain areas that are activated by the delivery of primary reinforcers such as appetitive stimuli (Berns et al, 2001;McClure et al, 2003;O'Doherty et al, 2004), and secondary reinforcement such as monetary gains and losses (Breiter et al, 2001;Delgado et al, 2004;Elliott et al, 2000;Holroyd et al, 2004b;Thut et al, 1997). However, it remains to be determined precisely how information about reward and punishment is encoded in these reward-sensitive neural circuits.…”
mentioning
confidence: 99%